Quality Micro-decision-making at Selected Philippine Public Secondary Schools: An Iterative Process of Planning and Implementing the Curriculum - Biñas, Joana Paula; Siason, Nordy; Paulino, Rex (Journal of Humanities and Social Sciences Studies, 2023)
The Philippine K to 12 Basic Education Curriculum advances with the trends and developments in society and adapts to the sudden shifts of demands and restrictions for the effective delivery of a 21st–century education. The onset of School-Based Management (SBM) has given birth to rapid changes in the Department of Education (DepEd) these past years. Through the SBM, micro-level decision-making has been made to address the unique issues faced by a school which eventually developed a strategy for maximizing local resources for school development. The School Improvement Plan (SIP) has answered the continuing complexities in school management, notwithstanding the volatile education landscape in the new normal. This exploratory multiple case study looked into five (5) selected public secondary schools in the Philippines. It also uncovered constraints in setting plans and empowering the stakeholders to forge a larger school community. Data sources were survey questionnaires, semi-structured interviews, and document analysis through the school records. Considering different school categories, populations of learners and teachers, and types of educational leadership, the different views of educational institutions on planning improvements vis-à-vis the DepEd-mandated procedures on formulation and implementation of the SIP surfaced from the data. It is hoped that the investigation’s findings provide meaningful insights into crafting strategies to highlight the essence of stakeholders’ participation, especially in the planning phase. Although results revealed that schools’ have varied ways of making a SIP, each considered an informed, community-based preparation stage as an arduous capsulized plan, with an end in mind, to achieve an outcomes-based education. Notably, all DepEd schools share one set of vision, mission, and core values. School leadership matters the most in such an iterative process. Hence, school heads and their leadership style must cater to flexibility in contextualizing not only the SIP formulation but also its implementation.